Effective supervision for the helping professions - Carroll, Michael (Sage Publications India Pvt Ltd, 2014)
Using features such as case studies, exercises and points for reflection, this is an ideal introduction to managing the supervisory relationship for both trainee and supervisor. This second edition of the book formerly titled 'Counselling supervision' now covers new and contemporary areas of supervision such as ethical maturity, insights into supervision from neuroscience and the organisational demands from the various contexts in which supervision takes place. It widens the concept of supervision to include professions such as coaching, organisational development consulting, counselling and psychology.